(untitled) (Bangladesh Journal of Plant Taxonomy, 2019)
Glaucium taxa were investigated in terms of their morphological, palynological and phylogenetical characteristic. The results of this study show differences between the taxa in some of these characteristics, especially in micromorphology and formation of clades in phylogenetic trees based on the matK and ITS3-6 DNA sequence data. Based on the findings of the molecular analyses supported by morphological data (stem’s trichomes), the genus Glaucium of Turkey was divided into subsections Glabrousae and Pubescentae.